The Facts, Concepts, and Generalizations in Social Studies Learning - Sari, Fitria; Sundari , Anggun; Putri , Alvina Handayani; Putra, Alviyanda Eka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Integrating Social Studies (IPS) into the school curriculum aims to develop students into good citizens. This goal can be achieved if the learning conducted in schools leads to meaningful learning, allowing students to connect the material to real-life behavior. To achieve this, teachers need to design lessons that begin with facts, concepts, and generalizations. Generalization is a cognitive process that allows individuals to draw conclusions from limited experiences and apply them to new situations. Generalization is essential in every subject, aiming to draw conclusions that link the material to the contextual conditions in students' daily lives. Emphasizing generalization in Social Studies aims to connect the material to actions that need to be taken in social life. The importance of generalization in Social Studies learning is closely related to the goal of Social Studies, which is to make students good citizens.